Molecular characterization of Cryptosporidium spp. in calves (Bos taurus and Bos indicus) in the Formiga city, Minas Gerais - Brazil - Roberto César Araujo Lima; Monally Conceição Costa Aquino; Sandra Valéria Inácio; Milena Araúz Viol; Anaiza Simão Zucatto; Luiz da Silveira Neto; Bruno César Miranda Oliveira; Edvânia Nunes Vasconcelos; Katia Denise Saraiva Bresciani; Gilson Pereira Oliveira; Alvimar José Costa (Semina: Ciências Agrárias, 2014)
Cryptosporidiosis is a waterborne disease, has as aggravating the difficulty of preventing environmental contamination and lack of effective therapeutic measures. With marked importance to the cattle, causes inflammation and intestinal villous atrophy resulting in loss of absorptive surface. This study aimed to perform molecular characterization of Cryptosporidium spp. in calves in the city of Formiga, Minas Gerais. A total of 300 faeces samples from Holstein calves, Nelore and indefinite breed, both healthy, were evaluated by negative contrast staining technique of malachite green and through the reaction of nested PCR for amplification of DNA fragments of the 18S subunit of the RNA gene ribosomal. Occurrence of 5.33 % ( 16/300 ) for malachite green and 4.66 % ( 14/300 ) by PCR was observed, whereas no correlation was found between positive and variables studied. Through molecular characterization were identified Cryptosporidium andersoni and Cryptosporidium ryanae species. In conclusion, we observed a low incidence of infection and elimination of Cryptosporidium spp. oocysts, the absence of clinical signs in animals, strong agreement between the results obtained by the two techniques. Beyond, with the molecular characterization ( nested PCR ), species of C. andersoni and C. ryanae were diagnosed in age groups not present in the literature. These two species of Cryptosporidium are described above for the first time parasitizing cattle in the state of Minas Gerais.